Evaluation of Curriculum in Master of Education Program in Educational Administration Rajapruk University Using CIPPIEST Model - เพชรโรจน์ ลัดดาวัลย์ (Journal of Humanities and Social Sciences, Rajapruk University, 2019)
The objectives of this research were to evaluate the characteristics and evaluate the context, input, process, product, impact, effect, sustainability, and transportability of the teaching and learning systems of the Master of Education Program in Educational Administration at Rajapruk University. The sample was comprised of 77 persons including instructors, master graduates and master graduate employers. The data was collected by questionnaires and interview forms which were analyzed using frequency, percent, mean, standard deviation and content analysis. The research results found that as following: 1. Evaluation results, of the Master of Education Program in Educational Administration from master graduates, rank the highest in the subject of theories and educational administration principles. They had opportunity and progress in working, were able to work hard, and had critical, synthesis, and creative thinking skills. They could also adapt themselves and were efficient in communication. The motivation and satisfaction to study at Rajapruk University was influenced the famous qualities and advice of the instructors. The master graduate employers evaluated that the characteristics ranked highest were morals and ethics, followed by responsibility, inter-personal skills, having a volunteering mindset and concern for social development, having knowledge, ability, and intellectual skills, and a high level in numerical analysis, communication and using information skills. 2. The result from the context and input evaluation showed that the context had been situation and most instructors had a Ph.D. and held an academic rank as an associate professor. The process results emphasized in theories and strengthening leadership practices. The product evaluation showed that all students made a thesis, presented at the journal/national conference and had the highest satisfaction in learning and teaching system. The effective of outcome evaluation was all master graduates got jobs. The impact evaluation was that some graduates had a higher work position and continued their education with a Ph.D. at a government university. The work was sustainable by having an e-learning online program. The transportation was dispread using technology in the MBA and MPA programs.